Performance Test of Three-Phase Brushless Direct Current Motor Axial Flux with Different Diameter of Neodymium Type Permanent Magnet - Nurmalia, Alif; Hadi, Widyono; Cahyadi, Widya (ELKHA : Jurnal Teknik Elektro, 2021)
Technology that is growing rapidly and innovations that have sprung up in the electrical field today are driving the use of electricity as a source of energy to do work. Electric motor is one component that is very popular in the industrial world and households that are useful to human life. In addition to DC motors and induction motors, there are also 3 phase brushless direct current (BLDC) motors which are a type of synchronous motor where magnetic fields are produced by rotor and stator at the same frequency. The rotor is a moving part of the brushless direct current motor which is a place of permanent magnet called a pole. This paper discusses the performance of brushless direct current 3 phase axial flux motors with different diameters of neodymium type permanent magnets. Tests carried out using neodymium permanent magnets with diameters of 15mm x 2mm and 20mm x 2mm were tested without using a load and using load. The parameters used in testing motor performance include speed, torque, and motor power with a source voltage of 12V, 16V, 20V, and 24V. The test results shows that the speed value of a BLDC motor using permanent magnets with a size of 20mm x 2mm is greater than that of permanent magnets of 15mm x 2mm. The same thing applies to the value of the power produced while, for the value of torque when the motor uses a permanent magnet of 15mm x 2mm will be greater than that of a motor using a permanent magnet of 20mm x 2mm.